47.6k views
1 vote
Solve the equation 5x+(-2)=6x+4

User Almond
by
6.5k points

2 Answers

2 votes

Answer:

x = -6

Explanation:


5x+(-2)=6x+4

Open the parenthesis


+(-2) =-2\\\\5x -2 =6x+4

Collect like terms and simplify


5x-6x =4+2\\-x =6

Multiply through by -1


-1(-x)=-1(6)\\\\x = -6

User Balder
by
5.3k points
1 vote

Answer:

x = -6

Explanation:

Step 1: Write out equation

5x + (-2) = 6x + 4

Step 2: Simplify

5x - 2 = 6x + 4

Step 3: Subtract 5x on both sides

-2 = x + 4

Step 4: Subtract 4 on both sides

-6 = x

Step 5: Rewrite

x = -6

User Jhun
by
5.5k points